2020
DOI: 10.21203/rs.3.rs-21652/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic and immune roles of synaptotagmin-4 in gastric cancer and brain lower-grade glioma

Abstract: Background Synaptotagmins (SYTs) are a family of proteins whose primary function is serving as a calcium sensor in vesicle transport and exocytosis, playing an important role in the function of immune cells. There is also a close relationship between immune cells and tumours. SYT4 is one molecule involved in this relationship, but the relationship between SYT4 and cancer remains unclear. Therefore, we hypothesize that SYT4 can affect the prognosis of cancer, and may be related to immune cells. Methods The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…In terms of potential treatments, Klinger et al [ 31 ] found that drugs targeting the cyclin-dependent kinase 6 (CDK6) are important for treating patients with this disease. Müller et al [ 32 ] discovered that SYT4 was down-regulated after a SARS-CoV-2 infection; however, while the authors establish a link between this gene and beta-cell physiology or diabetes, other authors, such as Jiang et al [ 33 ], discovered a link between this gene and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of potential treatments, Klinger et al [ 31 ] found that drugs targeting the cyclin-dependent kinase 6 (CDK6) are important for treating patients with this disease. Müller et al [ 32 ] discovered that SYT4 was down-regulated after a SARS-CoV-2 infection; however, while the authors establish a link between this gene and beta-cell physiology or diabetes, other authors, such as Jiang et al [ 33 ], discovered a link between this gene and immune cells.…”
Section: Discussionmentioning
confidence: 99%